From Worldview to Institution: Ungku Aziz and the Moral Foundations of Malaysia’s Development Trajectory - Muhammad Suhaimi; Fuadah Johari; Nuur Halimatus Sa'adiah Masrukhin; Zul Aizat Hamdan; Zulfi Akmal (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Purpose – This study examines why the moral worldview of Ungku Aziz remains important for understanding Malaysia’s development trajectory. Existing scholarship has often interpreted Malaysian development through technocratic, macroeconomic, or administrative lenses, while giving less attention to the ethical ideas that informed institutional design. Building upon earlier studies on Ungku Aziz as an economist and public intellectual, this article argues that his key contribution was the translation of justice-oriented values into practical development institutions. The study, therefore, reinterprets him as an architect of morally grounded development rather than merely a policy technocrat. Design/Methods/Approach – The study employs a qualitative research design, utilizing textual and thematic analysis. Primary materials comprise selected writings, speeches, policy commentaries, and public interventions by Ungku Aziz across various periods. These are supplemented by secondary literature on Malaysian development, poverty studies, Islamic moral economy, and institutional theory. The materials were coded thematically to identify recurring concepts such as distributive justice, dignity, education, rural upliftment, and public responsibility, before tracing their institutional manifestations in the Malaysian context. Findings – The study finds that Ungku Aziz consistently framed development as a human-centred and ethical process rather than a narrow exercise in income expansion. His thought linked poverty reduction with structural reform, educational mobility with national advancement, and state capacity with distributive fairness. The findings indicate that values such as justice, dignity, and social responsibility were reflected in policy orientations relating to poverty alleviation, rural advancement, and institutional nation-building. This supports the argument that Malaysia’s development experience cannot be understood solely through economic management, but also through normative foundations that shaped policy priorities. Research Implications/Limitations – The study is based primarily on documentary interpretation rather than direct causal measurement of policy outcomes. As such, the findings are strongest in explaining the relationship between ideas, institutional orientation, and development discourse rather than quantifying policy effectiveness. The qualitative design also limits broader generalisation beyond the Malaysian case. Future research may employ comparative or mixed-method approaches to test how ethical worldviews influence measurable development outcomes across other national settings. Originality/Value – This article contributes to scholarship by repositioning Ungku Aziz as a thinker of moral institutionalism whose ideas bridged ethics and governance. It adds to debates in Islamic moral economy, development theory, and Malaysian political economy by showing how value-based worldviews can be translated into modern state institutions within a plural society. The study also offers a conceptual basis for future research on inclusive and human-centred development in contemporary Asia.